Drosophila ATP6AP2/VhaPRR functions both as a novel planar cell polarity core protein and a regulator of endosomal trafficking. (4th January 2013) - Hermle, Tobias; Guida, Maria Clara; Beck, Samuel; Helmstädter, Susanne; Simons, Matias
<x xml:space="preserve">Abstract</x> Planar cell polarity (PCP) controls the orientation of cells within tissues and the polarized outgrowth of cellular appendages. So far, six PCP core proteins including the transmembrane proteins Frizzled (Fz), Strabismus (Stbm) and Flamingo (Fmi) have been identified. These proteins form asymmetric PCP domains at apical junctions of epithelial cells. Here, we demonstrate that VhaPRR, an accessory subunit of the proton pump V‐ATPase, directly interacts with the protocadherin Fmi through its extracellular domain. It also shows a striking co‐localization with PCP proteins during all pupal wing stages in Drosophila. This localization depends on intact PCP domains. Reversely, VhaPRR is required for stable PCP domains, identifying it as a novel PCP core protein. VhaPRR performs an additional role in vesicular acidification as well as endolysosomal sorting and degradation. Membrane proteins, such as E‐Cadherin and the Notch receptor, accumulate at the surface and in intracellular vesicles of cells mutant for VhaPRR. This trafficking defect is shared by other V‐ATPase subunits. By contrast, the V‐ATPase does not seem to have a direct role in PCP regulation. Together, our results suggest two roles for VhaPRR, one for PCP and another in endosomal trafficking. This dual function establishes VhaPRR as a key factor in epithelial morphogenesis.